1971
DOI: 10.1254/jjp.21.377
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Taxifolin

Abstract: (5) is shown in Fig. 1. FIG. 1. Taxifolin (Di-hydro quarcetin) METHODSAnti-inflammatory studies The animals used in this study were adult albino rats weighing between 80 and 100 g. They were divided into batches of six animals each except in the case of cotton pellet implantation for which groups of four animals were used. Carrageenin-incluced oedema: Freshly prepared suspension of carrageenin, 0.05 ml (1.0 % in 0.9 % saline) was in jected under the plantar aponeurosis of right hind paw of the rats by the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The exact chemical constituent/s of Bryophyllum pinnatum that is/are responsible for the observed antinociceptive, anti-inflammatory and hypoglycaemic effects of the plant's leaf aqueous extract still remain/s speculative. However, a number of investigators have shown that a host of secondary plant metabolites with diverse chemical structures possess the latter properties in various experimental animal models (Gupta et al, 1969(Gupta et al, , 1971Sugishta et al, 1982;Singh et al, 1992;Price et al, 1987;Simon et al, 1992;Liu, 1995;Marles and Farnsworth, 1995;Ojewole, 2002bOjewole, , 2003Dongmo et al, 2003;Taesotiku et al, 2003;Adzu et al, 2003;Li et al, 2003;Akah and Okafor, 1992;Marles and Farnsworth, 1995). Since the leaves of Bryophyllum pinnatum are known to contain flavonoids, polyphenols, triterpenoids and phytosterols, it is not unreasonable to speculate that these chemical compounds might have contributed to the observed antinociceptive, anti-inflammatory and hypoglycaemic effects of the herb.…”
Section: Discussionmentioning
confidence: 99%
“…The exact chemical constituent/s of Bryophyllum pinnatum that is/are responsible for the observed antinociceptive, anti-inflammatory and hypoglycaemic effects of the plant's leaf aqueous extract still remain/s speculative. However, a number of investigators have shown that a host of secondary plant metabolites with diverse chemical structures possess the latter properties in various experimental animal models (Gupta et al, 1969(Gupta et al, , 1971Sugishta et al, 1982;Singh et al, 1992;Price et al, 1987;Simon et al, 1992;Liu, 1995;Marles and Farnsworth, 1995;Ojewole, 2002bOjewole, , 2003Dongmo et al, 2003;Taesotiku et al, 2003;Adzu et al, 2003;Li et al, 2003;Akah and Okafor, 1992;Marles and Farnsworth, 1995). Since the leaves of Bryophyllum pinnatum are known to contain flavonoids, polyphenols, triterpenoids and phytosterols, it is not unreasonable to speculate that these chemical compounds might have contributed to the observed antinociceptive, anti-inflammatory and hypoglycaemic effects of the herb.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the exact chemical constituent/s of H. hemerocallidea corm that is/are responsible for the observed antinociceptive, anti-inflammatory and antidiabetic effects of the 'African Potato' aqueous extract is/are still obscure. However, a number of investigators have shown that a host of secondary plant metabolites with diverse chemical structures possess the latter properties in various experimental animal models (Gupta et al, 1969(Gupta et al, , 1971Sugishta et al, 1982;Price et al, 1987;Singh et al, 1992;Akah and Okafor, 1992;Simon et al, 1992;Liu, 1995;Marles and Farnsworth, 1995;Dongmo et al, 2003;Taesotiku et al, 2003;Adzu et al, 2003;Li et al, 2003). Since H. hemerocallidea corms are known to contain large quantities of phytosterols and sterolins, it is not unreasonable to speculate that these chem- 18.45 ± 1.41 15.74 ± 1.40 * 11.60 ± 1.36 ** 8.78 ± 1.35 *** 11.83 ± 1.38 ** 9.67 *** 52.41 *** Chlorpropamide (250 mg/kg p.o.…”
Section: Discussionmentioning
confidence: 99%
“…Since Sclerocarya birrea stem-bark is known to contain triterpenoids, flavonoids and phytosterols (in addition to other chemical compounds), it is not unlikely that these chemical compounds might have contributed to the observed analgesic, anti-inflammatory and hypoglycaemic effects of the plant's stem-bark aqueous extract. Several investigators have indeed attributed the anti-inflammatory and hypoglycaemic properties of a number of plants to their triterpenoid, coumarin and flavonoid constituents (Gupta et al, 1969;1971;Sugishta et al, 1982;Price et al, 1987;Simon et al, 1992;Singh et al, 1992;Liu, 1995;Marles and Farnsworth, 1995;Ojewole, 2002;2003). Since Sclerocarya birrea stem-bark has been widely reported to contain many chemical compounds, including polyphenols, tannins and flavonoids, sterols, triterpenoids, sesquiterpenes, ascorbic acid, oleic acid, myristic, stearic, glutamic and amino acids, and so on, it may be reasonable to speculate that the analgesic, anti-inflammatory and anti-diabetic properties of the plant extract observed in this study could be due respectively, to one or more of the above chemical constituents of the plant.…”
Section: Discussionmentioning
confidence: 99%